Comparison between isobaric levobupivacaine 0.5% and hyperbaric bupivacaine 0.5% in spinal anesthesia in lower limb surgeries and lower abdominal surgeries in adult patients - Parashar, Preeti; Singh, Anisha; Sharma, Manoj Kumar; Raval, Dipak L. (International Journal of Research in Medical Sciences, 2021)
Background: The aim of our study was to compare sensory and motor block characteristics and hemodynamic changes following intrathecal hyperbaric bupivacaine (0.5%) and isobaric levobupivacaine (0.5%) in elective lower limb and lower abdominal surgeries. Methods: 60 patients of either sex, aged 18-60 years, ASA grade I or II scheduled for elective lower abdominal and lower limb surgeries were randomized into two groups, group B (n=30) and group L (n=30) and received either 3 ml of intrathecal hyperbaric bupivacaine or isobaric levobupivacaine intrathecally. Results: The mean time of onset of sensory block at shin of tibia in both the groups was comparable i.e. levobupivacaine (1.19±0.2 minutes) and bupivacaine (1.1+0.2 minutes). The mean time for total duration of sensory block was 211.1±8.2 minutes in group L, while 193.13±13.7 minutes in group B. Time for total duration of motor block in group L was 198.76±8.428 minutes and in group B was 182.6±13.989 minutes. Statistically significant difference was observed in total duration of sensory and motor block in both levobupivaciane and bupivacaine group (p<0.0001). Patients in group L were hemodynamically more stable with significantly less decrease in pulse rate, systolic blood pressure and diastolic blood pressure as compared to group B. Conclusions: We observed that 0.5% isobaric levobupivacaine provided better hemodynamic stability, longer duration of sensory and motor block as compared to bupivacaine.